Endotracheal intubation using video laryngoscopy causes less cardiovascular response and less airway morbidity compared to classic direct laryngoscopy during surgery.direct laryngoscopy during surgery (Bangladesh Critical Care Journal, 2022)
Introduction: Endotracheal intubation using video laryngoscopy causes less cardiovascular response and less airway morbidity compared to classic direct laryngoscopy, in cardiac surgery. A comparison of the cardiovascular responses to endotracheal intubation using both indirect video laryngoscopy and direct laryngoscopy within the same patient has not yet been described.Materials and methods: This comparative randomized controlled clinical trial on 110 patients undergoing elective CABG. Data were expressed as mean ± SD and statistically analyzed using analysis of variance (ANOVA) and paired “t”-test over time and software SPSS-19.00.Results: Total intubation time was significantly higher in Video laryngoscopy group than direct laryngoscopy group (Table 2). The mean effective airway time were 6.15±4.92 in Video laryngoscopy group and 11.32(±9.11) in direct laryngoscopy group which was statistically significant (Table 3). The relative increase of the Rate Pressure Product (RPP) at intubation was significantly smaller (i.e. 27%, P < 0.001) using video laryngoscopy compared to the classic direct laryngoscopy. Cardiovascular responses were blunted by an additional 10. 2% (P = 0.029), when the patient was on beta blockade (Table 4). Conclusion: Study observed that less hemodynamic responses during endotracheal intubation using indirect video laryngoscopy compared to classic direct laryngoscopy. Even if the patient is on beta-blocker therapy, diminished cardiovascular responses at intubation were recorded after indirect laryngoscopy compared to direct laryngoscopy.Bangladesh Crit Care J March 2022; 10 (1): 52-56